REPRESENTASI NILAI BUDAYA DALAM ANALISIS KUALITATIF KEHIDUPAN KELUARGA TOKOH UTAMA DRAMA CHINA THE FIRST FROST - Kamila Zahra Hapsari; Wandayani Goeyardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the growing popularity of Chinese dramas as a global medium that functions not only as entertainment but also as a means of representing cultural values, particularly in the context of family life rich in social meaning. One of the notable dramas is The First Frost, which portrays the life dynamics of the main female character, Wen Yifan, through various emotional experiences and complex social relationships. This study aims to analyze how cultural values are represented in the family life of the character.The method used is a descriptive qualitative approach with cultural representation analysis through observation of scenes, dialogues, and interactions between characters. The results and discussion show that the representation of cultural values in this drama is manifested in three main dimensions: the essence of life, depicted through experiences of loss and suffering; the perception of time, influenced by past experiences that shape individuals’ perspectives on present life; and human relationships, portrayed through various forms of interaction, including hierarchical, supportive, and socially pressured relationships. These values are not conveyed explicitly but are constructed through representational practices that symbolically shape meaning.The conclusion of this study is that The First Frost selectively represents cultural values through the experiences of the main character, indicating that audiovisual media not only reflects social reality but also actively constructs and transmits cultural meanings.